3D CVD Graphene Oxide on Ni Foam towards Hydrogen Evolution Reaction in Acid Electrolytes at Different Concentrations. (5th April 2018) - Sarawutanukul, Sangchai; Phattharasupakun, Nutthaphon; Wutthiprom, Juthaporn; Sawangphruk, Montree
Abstract : Thin layers of graphene and graphene oxide coated on nickel foam substrate was synthesized by a chemical vapor deposition method and used as a hydrogen evolution reaction (HER) catalyst in acidic condition. The graphene oxide carbocatalyst with oxygen functional groups, large amounts of active sites, and hydrophilic property exhibits superior HER activity as compared to the pristine nickel foam and graphene. The graphene oxide coated on nickel substrate exhibits an overpotential of -83.2 mV vs. RHE at a current density of 10 mA cm - 2 and an excellent electrochemical stability up to 7 hours in 1.0 M H2 SO4 . In addition, the effect of electrolyte concentrations was also studied in 0.1, 0.5, 1.0, and 2.0 M H2 SO4 . At high concentration, the HER activity is higher because large amounts of protons can increase the ionic conductivity in the electrolyte and can participate in the reaction generating more hydrogen when compared to the lower concentration. We believe that the graphene oxide-coated Ni electrode, which can be operated in an acidic environment, can be practically used as an alternative electrocatalyst towards HER.